Comparing the Impact of Problem Solving vs. Problem Posing Approaches on Mathematics Achievement in Junior High School - Wirnayanti, Wirnayanti; Craig, Jeffrey; Malatjie, Jeffrey Fourrie (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this research is to describe students' mathematics learning outcomes using a problem solving approach, describe students' mathematics learning outcomes using a problem posing approach, and to find out differences in mathematics learning outcomes between those using the problem solving and problem posing approaches. Methodology: This research is a type of quasi-experimental research with the Nonequivalent Posttest-Only Control Group Design. The population in this research is all students of class VIII junior high school Muhammadiyah 1 Makassar in the 2018/2019 academic year and the sample from this research consists of 2 classes, where the two classes will receive different treatment, namely the first class uses the Problem Solving approach and the second class uses the Problem Posing approach, with a total of 25 students for the Problem Solving approach and also 25 students for the Problem Posing approach. Main Findings: The results of this research are that there are differences in the average results of learning mathematics through the Problem Solving approach and the Problem Posing approach. Where in the Problem Solving approach the average learning outcome value is 82.96 with a standard deviation of 4.78, and the average learning outcome in the Problem Posing approach is 87.88 with a standard deviation of 7.36. Novelty/Originality of this study: This study provides new insights into how problem solving and problem posing approaches affect the mathematics learning outcomes of grade VIII students.